2018
DOI: 10.1002/ceat.201700527
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Porosity of Molded Calcium‐Based Sorbents by Glucose Templating for Cyclic CO2 Capture

Abstract: With the aim to enhance the CO2 capture capacity and anti‐attrition property of CaO‐based sorbents simultaneously, a novel CaO‐based sphere was prepared by extrusion‐spheronization using Ca(OH)2 powder with glucose templating. The CO2 capture characteristics and attrition resistance property of the sorbent were examined and the microstructure of the sorbents was analyzed. The results demonstrate that the obtained spherical sorbents exhibit an outstanding anti‐attrition performance compared to limestone sorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…CO 2 in flue gas is absorbed by CaO sorbents (transformed into CaCO 3 in a carbonator), and then the CaO is regenerated from CaCO 3 in a calcinator, where a pure CO 2 steam is produced, which can be utilized or geologically isolated. Compared to other absorption technologies, this technique consists of a host of inherent thermodynamic merits such as high CO 2 capture capacity 17 and being an abundant source, 18 which has attracted a large amount of research. However, the major disadvantage of this technique is sintering of CaO occurred during the long-term hightemperature reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…CO 2 in flue gas is absorbed by CaO sorbents (transformed into CaCO 3 in a carbonator), and then the CaO is regenerated from CaCO 3 in a calcinator, where a pure CO 2 steam is produced, which can be utilized or geologically isolated. Compared to other absorption technologies, this technique consists of a host of inherent thermodynamic merits such as high CO 2 capture capacity 17 and being an abundant source, 18 which has attracted a large amount of research. However, the major disadvantage of this technique is sintering of CaO occurred during the long-term hightemperature reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Internal compressive stress caused by the rapid release of CO 2 makes particles shrink in the calcination stage. The cracks are easy to form on the surface and inside of CaO materials under the repeated action of chemical and internal compressive forces . Therefore, it is necessary to examine the macrostructural integrity of the CaO honeycomb after different cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al developed the different pore-forming materials, such as cellulose, 37 rice husk, 38 and microalgae, 39 to enhance the CO 2 capture capacity of CaO-based pellets fabricated by the extrusion−spheronization method. Xu et al 40 prepared CaO-based pellets via the extrusion−spheronization method for CO 2 capture and found that these pellets possessed higher mechanical strength compared to limestone. However, the mechanical properties and heat storage capacities of CaO-based pellets prepared by the extrusion−spheronization method during the CaO/CaCO 3 TCHS cycles have not been reported.…”
Section: Introductionmentioning
confidence: 99%